Technical and Allocative Efficiency of Poultry Egg Producers in Nigeria (2011)
This study carried out an analysis of the determinants of efficiency among poultry egg farmers in Jos metropolis of Plateau state, Nigeria. A three stage random sampling technique was used in collecting the data used for this study. The study shows clearly that farm size and cost of drugs are the most important inputs in poultry egg production in the area. About 69% variation in the output of poultry egg production was found to be due to the technical inefficiency of the farmers. Technical efficiency of poultry egg farmers in the study area was found to be high with a mean of 94.2%. Further, analysis reveals that the intensity of output (total production), average price of feed, price of drugs, capital input and cost on utilities are the determinants of allocative efficiency while farming experience and access to credit facilities have significant impact on cost inefficiency. The study recommended the need for stakeholders in poultry egg production to intensify effort in ensuring farmers access to credit and extension services and also sensitize farmers with respect to the right level of input combinations that can improve efficiency level of poultry egg production in Nigeria